Advanced small cell carcinoma of the bladder: clinical characteristics, treatment patterns and outcomes in 960 patients and comparison with urothelial carcinoma. (18th December 2015) - Geynisman, Daniel M.; Handorf, Elizabeth; Wong, Yu‐Ning; Doyle, Jamie; Plimack, Elizabeth R.; Horwitz, Eric M.; Canter, Daniel J.; Uzzo, Robert G.; Kutikov, Alexander; Smaldone, Marc C.
Abstract : Advanced small cell carcinoma of the bladder is a rare disease with a poor survival and palliative therapy is common, especially in M1 patients. In comparison to urothelial carcinoma, the outcomes for small cell bladder patients are worse in those with lymph node only involvement but equivalent in those with distant disease. Abstract: To describe the clinical characteristics, treatment patterns and outcomes in advanced small cell bladder cancer (aSCBC) patients and compare to those with urothelial carcinoma (UC). Individuals in the National Cancer Data Base with a diagnosis of either nodal (TxN+M0) or distant metastatic (TxNxM1) disease were identified from 1998 to 2010. We assessed the relationships between stage, treatment modalities and survival in the aSCBC cohort and compared these to UC patients. In the 960 patient aSCBC cohort (62% M1), 50% received palliative therapy alone, 68% in M1 versus 21% in M0 groups ( P < 0.0001). Single modality local therapy (15%) and surgical (21%) or radiation‐based (14%) multimodal therapy (MMT) were used in the other 50%. Cystectomy‐based MMT was utilized in 45% of N+M0 versus 6.4% of NxM1 patients ( P < 0.0001). Median overall survival (OS) for aSCBC patients was 8.6 months; 13.0 months in N+M0 versus 5.3 months in NxM1 patients ( P < 0.0001). Survival was similar between TxN1M0 and TxN2‐3M0 patients (14.8 months vs. 12.1 months, P = 0.15). Urothelial carcinoma patients ( n = 27, 796, 45% M1) lived longer compared to aSCBC patients in the N+M0 group (17.3 months vs. 13.0 months, P = 0.0007). There were not clinically significant differences in OS between UC and aSCBC patients in the M1 group. Advanced SCBC is a rare disease with a poor survival and palliative therapy is common, especially in M1 patients. In comparison to UC, the outcomes for aSCBC patients are worse in those with lymph node only involvement but similar in those with distant disease.